Geração de trabalho e renda de forma sustentável através da economia solidária: a experiência do Banco Palmas - Serpa, Luiz Carlos Moreira da Rocha (2008)
The work intended to analyze the case of the Bank Palmas as institution of micro-credit that acts in “Palmeiras”, a low-income neighborhood of Fortaleza – CE. According to the work it was showed that the socio-economic policy of micro-credit implemented by the Bank Palmas is capable to generate yield and job for the local population. For the development of this work was intended to deal with articles produced by the Brazilian net of supportive economy, as well like books, field work and matters about the Bank Palmas. From the facts collected in the field work, was used an econometric approach based in the “probit” models and of multiple regression with the objective of analyzing the impacts about the invoicing and the productivity of the companies/clients of the bank Palmas interviewed. The main results of these models are: The aid of the agents of the bank with his clients jointly with the experience of the clients as autonomous shatter of positive form in the invoicing of the companies analyzed, and the loan granted to these companies acts of straight form in the increase of productivity of the same. From that context was concluded that the general objective of the work was reached, therefore, was possible to establish the answers for the problem investigated, arriving to the conclusion of that to economic and social policy of micro-credit developed by the Bank Palmas is straightly related with the generation of income and labor supply of the resident population in Palmeiras. So, it was showed that in the bank there is a strategy of local socio-economic development whose protagonists left of their mere position of inhabitants for the ones of active citizens as collective subjects and that, on average, the loan granted by the bank Palms is of fundamental importance for the growth of the small companies that need the loans from the bank.